Philip in Text and Realia: Contextualising a Biblical Figure Within Roman Hierapolis - Wilson, Mark W. 1949- (2022)
The interrelationship between text and material culture is an ongoing discussion in academic studies. While early Christianity and classical archaeology often intersect in their respective fields of inquiry, they are often unaware of discussions and discoveries in each other’s discipline. This article discusses a biblical figure named Philip whose legacy is found in texts and realia related to the Phrygian city of Hierapolis in western Asia Minor. Biblical scholars have conducted a vigorous discussion about the identity of this Philip based on early Christian texts. Italian archaeologists have recently discovered a tomb and basilica in Hierapolis that they have associated with the apostle Philip. The discussion seeks to put these disciplines in dialogue by collocating the relevant texts and realia regarding this important biblical figure. The first section explores the prominence of two Philips in early Christian literature—the disciple/apostle Philip, particularly in the Gospel of John, and the deacon/evangelist Philip, particularly in Acts. Hierapolis was a major “pagan” pilgrimage destination with its sanctuaries of the Apollo temple and the Ploutonion. These were destroyed in Late Antiquity and replaced by a martyrium and basilica associated with a martyrdom tradition related to Philip. This monumentalisation around his tomb made Hierapolis an important Christian pilgrimage destination in Asia along with Ephesus.
Keywords: Pilgrimage; monumentalisation; Martyr; Hierapolis; Evangelist; Apostle; Philip